Factors affecting rind oil content of lemon (Citrus limon (L.) Burm. f.) - Van der Merwe, Hester E. (Hester Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2005.